Physical and Social Factors of Shoreline Change in Gebang, Cirebon Regency 1915 – 2019 - Millary Agung Widiawaty; Nandi Nandi; Hendro Murtianto (Journal of Applied Geospatial Information, 2020)
Shoreline changes are the main concern for coastal management. In Indonesia coastal zone is the populated region for marine and fishery economic sectors. Dynamic of the region shown by shoreline change. This study aims to explain the dynamics of shoreline change in Gebang, Cirebon Regency from 1915 to 2019, and several factors that influence. This research using overlay intersections to know shoreline change from 1915-2019 and multiple linear regression to determine several factors that influence the shoreline change. The shoreline increased 992.99 meters caused by accretion. Physical factors that influence shoreline changes include total suspended solids, bathymetry, wind, and tides, whereas social factors include the presence of beach building, population density, building density, and distance from the built-up area. The most influential factor in increased shoreline is bathymetry. Based on the results of statistical tests known that physical and social factors are influence significantly the dynamics of shoreline changes. The correlation between the actual and the predicted value reached 0.97 with p-value 0.001.